Modelling of sulphur amino acid requirements and nitrogen endogenous losses in kittens - Sato, Joyce; Merenda, Mônica Estela Zambon; Uemoto, Aline Terumi; Dos Santos, Mateus Pereira; Barion, Mariana Regina Lingiardi; Carciofi, Aulus Cavalieri [UNESP]; de Paula Dorigam, Juliano César [UNESP]; Ribeiro, Leonir Bueno; Vasconcellos, Ricardo Souza (Taylor & Francis, 2020)
The objective of this study was to estimate the sulphur amino acid (methionine + cystine) requirements and nitrogen endogenous losses in kittens aged 150 to 240 d. Thirty-six cats were distributed in six treatments (six cats per treatment) consisting of different concentrations of methionine + cystine (M + C): T1, 6.5 g/kg; T2, 8.8 g/kg; T3, 11.3 g/kg; T4, 13.6 g/kg; T5, 16.0 g/kg; and control, 6.5 g/kg. Diets were formulated by serial dilution of T5 (a diet relatively deficient in M + C but containing high protein concentrations) with a minimal nitrogen diet (MND). Thus, crude protein and amino acid concentrations in diets T1–T5 decreased by the same factor. The control diet was the T1 diet supplemented with adequate concentrations of M + C (6.5 g/kg; 8.8 g/kg; 11.3 g/kg; 13.6 g/kg and 16.0 g/kg). All diets were based on ingredients commonly used in extruded cat diets. Digestibility assays were performed for the determination of nitrogen balance. Nitrogen intake (NI) and nitrogen excretion (NEX) results data were fitted with an exponential equation to estimate nitrogen maintenance requirement (NMR), theoretical maximum for daily nitrogen retention (NRmaxT), and protein quality (b). M + C requirements were calculated from the limiting amino acid intake (LAAI) equation assuming a nitrogen retention of 45 to 65% NRmaxT. The NMR of kittens aged 150, 195, and 240 d was estimated at 595, 559, and 455 mg/kg body weight (BW)0.67 per day, respectively, and M + C requirements were estimated at 517, 664, and 301 mg/kg BW0.67 per day, respectively.
Keywords: cats; cystine; Göttingen method; kittens; methionine; nitrogen balance; requirements